Dysregulated CD4(+) T cells from SLE-susceptible mice are sufficient to accelerate atherosclerosis in LDLr(−/−) mice - Wilhelm, Ashley J (BMJ Publishing Group, 2015)
OBJECTIVE: Accelerated atherosclerosis is a major source of morbidity in systemic lupus erythematosus (SLE). However, the cause of SLE-accelerated atherosclerosis remains unclear. METHODS: CD4(+) T cells from C57/Bl/6 (B6) or SLE-susceptible B6.Sle1.2.3 (B6.SLE) mice were transferred into LDLr(−/−), Rag(−/−) mice. T cells were examined for cytokine production and expression of interleukin-10 receptor (IL-10R) and functional markers. T cells were isolated based on FoxP3(GFP) expression and transferred to LDLr(−/−), Rag(−/−) mice to establish a role for B6.SLE effector T cells (T(eff)) in atherosclerosis. RESULTS: Mice receiving whole B6.SLE CD4(+) T cells displayed no other SLE phenotype; however, atherosclerosis was increased nearly 40%. We noted dysregulated IL-17 production and reduced frequency of IL-10R expression by B6.SLE regulatory T cells (T(reg)). Functional assays indicated resistance of B6.SLE T(eff) to suppression by both B6.SLE and B6 T(reg). Transfer experiments with CD4(+)FoxP3(−) T(eff) and CD4(+)FoxP3(+) T(reg) from B6.SLE and B6 mice, respectively, resulted in increased atherosclerosis compared with B6 T(eff) and T(reg) recipients. T(reg) isolated from mice receiving B6.SLE T(eff) with B6 T(reg) had increased production of IL-17 and fewer expressed IL-10R compared with B6 T(eff) and T(reg) transfer. CONCLUSIONS: Transfer of B6.SLE T(eff) to LDLr(−/−), Rag(−/−) mice results in accelerated atherosclerosis independent of the source of T(reg). In addition, the presence of B6.SLE T(eff) resulted in more IL-17-producing T(reg) and fewer expressing IL-10R, suggesting that B6.SLE T(eff) may mediate phenotypic changes in T(reg). To our knowledge, this is the first study to provide direct evidence of the role of B6.SLE T(eff) in accelerating atherosclerosis through resistance to T(reg) suppression.